Does NZ IFRS 38 Impact Equity Values and Borrowing Capabilities? Evidence from New Zealand - Ramachandra, Suresh (Asian Journal of Business and Accounting, 2017)
This paper explores the impact of NZ IFRS 38 on equity values and borrowing capabilities in publicly listed companies of New Zealand. Compliance with NZ IFRS 38 was expected to significantly alter the values of assets recognised in financial statements from those that were recognised under the NZ GAAP. Empirical data collected from the early adopters of this standard, provided a convenient means to infer the possible impacts that the standard could have had on equity values and borrowing capabilities. Employing Return on Assets (ROA) and Market to Book (MB) ratios as proxies for shareholder values, and Debt to Assets (DA) and current ratio (CA/CL) as proxies for borrowing capabilities of firms, equality of means was tested between the pre adoption period (2002â€2004) and the post adoption period (2005â€2007). Using nonâ€parametric testing of hypotheses, this research found no evidence to suggest that the post adoption values were any different from the pre adoption values. The findings of this research are expected to be of interest not only to standard setters in New Zealand but also to economies that are yet to adopt the IFRS fully. Keywords: NZ IFRS 38, International Financial Reporting Standards, Intangible assets, Equity, Borrowing capability, New Zealand